2020
DOI: 10.1136/bmjopen-2020-041989
|View full text |Cite
|
Sign up to set email alerts
|

Fibrosis-4 index as a predictor for mortality in hospitalised patients with COVID-19: a retrospective multicentre cohort study

Abstract: ObjectiveThe reliable risk factors for mortality of COVID-19 has not evaluated in well-characterised cohort. This study aimed to identify risk factors for in-hospital mortality within 56 days in patients with severe infection of COVID-19.DesignRetrospective multicentre cohort study.SettingFive tertiary hospitals of Daegu, South Korea.Participants1005 participants over 19 years old confirmed COVID-19 using real-time PCR from nasopharyngeal and oropharyngeal swabs.MethodsThe clinical and laboratory features of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
40
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 33 publications
5
40
1
Order By: Relevance
“…As we commented above, worse outcomes have been reported in patients with underlying liver disease and cirrhosis, it is easily speculated the subjects having higher FIB-4 are vulnerable to SARS-CoV-2 infection. Consistently to our results, Park et al [ 16 ] demonstrated that the survival rate was significantly lower in high FIB-4 group compare to the low FIB-4 group. These findings supported the predictive role of FIB-4 as we shown in our study, and would be useful to effective delivery of healthcare resources in COVID-19 pandemic era.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…As we commented above, worse outcomes have been reported in patients with underlying liver disease and cirrhosis, it is easily speculated the subjects having higher FIB-4 are vulnerable to SARS-CoV-2 infection. Consistently to our results, Park et al [ 16 ] demonstrated that the survival rate was significantly lower in high FIB-4 group compare to the low FIB-4 group. These findings supported the predictive role of FIB-4 as we shown in our study, and would be useful to effective delivery of healthcare resources in COVID-19 pandemic era.…”
Section: Discussionsupporting
confidence: 93%
“…Several pieces of evidence suggest the prognostic value of the FIB-4 index in COVID-19 cases [ 12 , 16 , 24 , 25 ]. Liver injury in COVID-19 cases has been observed more frequently in severe cases [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, elevation of this FIB-4 (equal or higher than 2.67) was associated with poor clinical outcomes in middle-aged patients with COVID-19, including required mechanical ventilation and ICU admission [ 22 ]. Moreover, FIB-4 was also related with increased risk of mortality in hospitalized patients with COVID-19 as well as with lower survival [ 23 , 24 ]. In addition, FIB-4 positively correlated to SARS-CoV-2 viral load and the levels of inflammatory cytokines [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although initially used as a marker of liver fibrosis, FIB-4 index has been repurposed for prognostication in patients with COVID-19, with or without liver disease [ 7 , 9 11 ]. Age, liver injury, and thrombocytopenia have been shown to increase mortality in COVID-19 [ 1 , 5 , 6 , 12 ].…”
Section: Resultsmentioning
confidence: 99%